BUDAYA ORGANISASI DAN TRANSFORMASI STRATEGIK: STUDI PADA PERUSAHAAN DI ERA DIGITAL - Bella Cahya Anggraini; Dosi Wiwit Hermawan; Restu Illa Dwinanda Dewana (Jurnal Riset Multidisiplin Edukasi, 2026)
The digital era has brought fundamental disruption that requires companies to undertake strategic transformation to maintain competitiveness. This research aims to analyze the role of organizational culture in driving strategic transformation of companies in the digital era by identifying the most significant cultural dimensions, exploring critical elements at each implementation stage, and explaining the dynamic interaction between cultural change and digital strategy evolution. The research employs a qualitative approach with a library research design on scientific publications from 2021-2026 analyzed through interpretive content analysis. The results show that organizational culture influences strategic transformation through three main dimensions: organizational adaptability, continuous learning orientation, and strategic collaboration. Critical elements facilitating success include transformational leadership, technology-strategy alignment, digital competency development, and continuous innovation culture. The dynamic interaction between culture and digital strategy demonstrates a recursive nature that forms a positive feedback loop. This research concludes that effective digital transformation requires a holistic approach integrating technology, human resources, and organizational culture systematically. Practical implications include a phased transformation roadmap and continuous investment in digital capability development to build organizational resilience in the digital era.